Infectious skin diseases in contact sports - a literature review - Kucharczyk, Natalia; Rak, Kacper; Jakoniuk, Maja; Kler, Katarzyna; Gaweł-Dąbrowska, Dagmara (Quality in Sport, 2025)
Introduction: Infectious skin diseases in athletes, particularly occur in contact sports like wrestling, football, and rugby and are caused by a variety of pathogens, including: bacteria, viruses, and fungi. These infections are common due to direct skin-to-skin contact and can lead to missed training and insufficient physical outcomes in competitions. The most frequent pathogens are methicillin-resistant Staphylococcus aureus, Trichophyton, and Herpes simplex virus. Skin infections often affect areas like the head, face, and arms and can be transmitted through contaminated equipment or direct contact. Prevention involves good hygiene, early detection, and proper disinfection of sports equipment. Effective management and isolation of infected athletes are key to reducing transmission. Purpose of the work: The aim of this review is to discuss common skin infections in contact sports, their prevalence, clinical features, diagnosis, treatment, and prevention strategies, categorized into bacterial, viral, and fungal infections. Materials and methods: A comprehensive analysis of research articles available on PubMed, Google Scholar, Web of Science, Embase, and Scopus was conducted using search terms related to: "contact sports," "skin infections," "infective skin diseases," "athletes" and "prevention." Results: Infectious skin diseases pose significant risks to athletes in contact sports due to close physical interaction, shared equipment, and skin injuries. Effective prevention requires strict hygiene, prompt wound care, and education on avoiding shared items. Awareness among coaches and athletes is crucial, as proper hygiene practices can reduce outbreaks. More research is needed to better understand transmission and to improve prevention strategies in contact sports.